Composition and Interface Engineering for Efficient and Thermally Stable Pb–Sn Mixed Low‐Bandgap Perovskite Solar Cells. (29th October 2018) - Chi, Dan; Huang, Shihua; Zhang, Meiying; Mu, Shaiqiang; Zhao, Yang; Chen, Yong; You, Jingbi
Abstract: Low bandgap lead–tin (Pb–Sn) mixed perovskite solar cells have achieved high power conversion efficiency in excess of 17%. However, methylammonium (MA) cation is usually contained, and the thermal stability of MA is always a great concern. In this work, according to composition engineering, a nearly formamidinium (FA) based low‐bandgap Pb–Sn mixed perovskite FAPb0.75 Sn0.25 I3 is being tried to explore as the absorber layer. Combined with interface engineering by replacing poly(3, 4‐ethylenedioxythiophene)‐polystyrenesulfonic acid (PEDOT:PSS), layer with NiO x as hole transport layer, a power conversion efficiency of 17.25% is obtained. This low‐bandgap perovskite solar cell maintains about 91% of its original efficiency at 80 °C for 20 h, and 92% of its initial performance after 46 days storage at the room temperature. The good thermal stability of nearly FA based low‐bandgap perovskite could be good for delivering efficient and stable perovskite‐perovskite tandem solar cells. Abstract : A nearly formamidinium (FA) lead–tin (Pb–Sn) mixed perovskite FAPb0.75 Sn0.25 I3 is exploited to fabricate a low‐bandgap perovskite solar cell. By combination with a NiO x hole transport layer, a power conversion efficiency of 17.25% is obtained. This low‐bandgap perovskite solar cell maintains about 91% of its original efficiency at 80 °C for 20 h, which demonstrates good thermal stability.